Massenet's Manon (Opera Journeys Mini Guide Series). - Fisher, Burton D. (Opera Journeys mini guide series., 2006)
A comprehensive guide to Massenet's MANON, featuring Principal Characters in the opera, Brief Story Synopsis, Story Narrative with Music Highlight Examples, and an insightful and in depth Commentary and Analysis by Burton D. Fisher, noted opera author and lecturer.